The Implementation of Employee Management System on SMC Technology Sdn. Bhd. - Loh, Chun Kang; Darman, Rozanawati (Applied Information Technology And Computer Science, 2022)
The employee management system is a platform that stores and manages all work-related as well as critical personal information of human resources in a secure environment. The aim of this study is to design, develop and test the web-based employee management system. This project employs a waterfall development method, and the system is built with Visual Studio Code and the phpMyAdmin as database. Employees and administrator are the two types of user in this system, and there are around five functional modules available, including employee information, attendance, leave, payroll, and performance. After the system is implemented, the user acceptance test and test plan are carried out, and the actual results also show that the test of each module is successful. In general, the system performs as a platform for improving employer-employee relationships, and also improve the performance of the company’s employee management.